Development of perovskite-based light emitting diodes with improved stability - Bala Saravana Nambiar Balan (2019)
All inorganic quantum dots due to their unique characteristics have narrow emission spectrum and size dependant emission wavelength. Perovskite nanocrystal are widely used in optoelectronic materials but the instability caused by the surface ions obstructs their application therefore, we used methods such as microwave irradiation and hot injection method to determine which was the best method to use in order to get a higher photoluminescence. We also used different surface ligands such as oleylamine and APTES to see which has a better PLQY. We also used oleylamine and APTES to test for thermal stability to determine which has perovskite has better stability or photoluminescence. And have concluded that using APTES as a surface ligand provides better stability but as the temperature increases the photoluminescence degrades as temperature increases therefore, different ligands is used for different application.